Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Answer:
- Reflected over the x-axis
- Compressed by a factor of 0.4.
- Translated 2 units left
Step-by-step explanation:
Given
[tex]y = \sqrt[3]{x}[/tex]
[tex]y' = -(0.4)\sqrt[3]{x-2}[/tex]
Required
The transformation from y to y'
First, y is reflected over the x-axis.
The transformation rule is:
[tex](x,y) \to (x,-y)[/tex]
So, we have:
[tex]y = \sqrt[3]{x}[/tex] becomes
[tex]y' = -\sqrt[3]{x}[/tex]
Next, it was compressed by a scale factor of 0.4
The rule is:
[tex]y' = k * y[/tex]
Where k is the scale factor (i.e. k = 0.4)
So, we have:
[tex]y' = 0.4 * -\sqrt[3]{x}[/tex]
[tex]y' = -(0.4)\sqrt[3]{x}[/tex]
Lastly, the function is translated 2 units left;
The rule is:
[tex](x,y) \to (x-2,y)[/tex]
So, we have:
[tex]y' = -(0.4)\sqrt[3]{x - 2}[/tex]
Answers:
-reflected over the x-axis
-translated 2 units right
-compressed by a factor of 0.4
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.